The nicking endonuclease N.BstNBI is closely related to Type IIs restriction endonucleases MlyI and PleI - Higgins, Lauren S. (Oxford University Press, 2001)
N.BstNBI is a nicking endonuclease that recognizes the sequence GAGTC and nicks the top strand preferentially. The Type IIs restriction endonucleases PleI and MlyI also recognize GAGTC, but cleave both DNA strands. Cloning and sequencing the genes encoding each of these three endonucleases discloses significant sequence similarities. Mutagenesis studies reveal a conserved set of catalytic residues among the three endonucleases, suggesting that they are closely related to each other. Furthermore, PleI and MlyI contain a single active site for DNA cleavage. The results from cleavage assays show that the reactions catalyzed by PleI and MlyI are sequential two step processes. The double-stranded DNA is first nicked on one DNA strand and then further cleaved on the second strand to form linear DNA. Gel filtration analysis shows that MlyI dimerizes in the presence of a cognate DNA and Ca(2+) whereas N.BstNBI remains a monomer, implicating dimerization as a requisite for the second strand cleavage. We suggest that N.BstNBI, MlyI and PleI diverged from a common ancestor and propose that N.BstNBI differs from MlyI and PleI in having an extremely limited second strand cleavage activity, resulting in a site-specific nicking endonuclease.